Pre-pregnancy inflammatory and insulinemic dietary patterns and risk of gestational diabetes mellitus: a prospective cohort study of 14,674 women - Peipei Liu; Jiaxi Yang; Deirdre K. Tobias; Fred K. Tabung; Frank B. Hu; Cuilin Zhang (BMC Medicine)
Abstract Backgroud Gestational diabetes mellitus (GDM) is associated with various short-term and long-term adverse health outcomes for both mothers and offspring. It is critical to identify modifiable factors that may inform the prevention of GDM. We, therefore, examined whether pre-pregnancy pro-inflammatory and hyperinsulinemic dietary patterns are associated with increased risk of GDM. Methods We included 14,674 women in the Nurses’ Health Study II who reported at least one singleton pregnancy between 1991 and 2001. We derived pre-pregnancy dietary pattern scores for empirical dietary inflammatory pattern (EDIP) and empirical dietary index for hyperinsulinemia (EDIH) from validated food frequency questionnaires collected before pregnancy. Incident first-time GDM was ascertained from self-report of a physician diagnosis with high validity. We used log-binomial models with generalized estimating equations to estimate the relative risks (RRs) and 95% confidence intervals (CIs) for the associations of pre-pregnancy EDIP and EDIH scores with GDM risk, adjusting for pre-pregnancy body mass index and other potential confounders. Results Participants reported 20,337 pregnancies over 10 years of follow-up, with 831 complicated by GDM. Women with higher pre-pregnancy EDIP and EDIH scores had a greater risk of GDM: adjusted RRs (95% CIs) for EDIP increasing quintiles were 1.00 (reference), 1.22 (0.97, 1.53), 1.19 (0.94, 1.49), 1.40 (1.13, 1.75), and 1.41 (1.13, 1.75); for EDIH were 1.00, 1.19 (0.94, 1.52), 1.21 (0.95, 1.54), 1.29 (1.02, 1.64), and 1.58 (1.26, 1.98) (both P-trend: <0.001). The observed associations were generally consistent across stratum of major risk factors of GDM such as pre-pregnancy overweight or obesity status, family history of diabetes, and genetic susceptibility of GDM. Conclusions In a large US cohort of predominantly White women, higher intake of pro-inflammatory and hyperinsulinemic diets was associated with increased risk of GDM. Further studies are warranted to confirm our findings, to provide evidence promoting anti-inflammatory and anti-hyperinsulinemic diets as a preventive measure for gestational diabetes in women planning pregnancy.